Traditional Sports for Enhancing Elementary Students’ Physical Fitness: A Quasi-Experimental Study - Hamdani Hamdani; Tien-Tsai Pan; Baxodir Madaminov (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the study: This study aimed to examine the effectiveness of traditional Indonesian sports activities as an alternative approach to improving the physical fitness of elementary school students compared to conventional Senam Kesegaran Jasmani (SKJ) exercises in primary school physical education settings.. Methodology: This study used a Pretest–Posttest Non-Equivalent Control Group quasi-experimental design (February–March 2025) involving 43 students (22 experimental, 21 control) from State Elementary School 1 Watugede, Kemusu, Boyolali. The Indonesian Physical Fitness Test (ages 6–9) and structured observations across 18 sessions were applied. Data were analyzed using Analysis of Covariance with pretest scores as covariate. Main Findings: The experimental group receiving traditional sports activities demonstrated higher physical fitness achievement than the control group following the standard SKJ program. Learning completion reached 63.64% in the experimental group and 52.38% in the control group. Psychomotor performance, student activeness, and discipline scores were also higher, with an effectiveness coefficient of 0.98, Cohen's d = 0.57 (medium effect), and partial eta-squared = 0.121, collectively confirming a statistically and practically significant improvement. Novelty/Originality of this study: This study introduces traditional Indonesian sports as a culturally grounded and play-based alternative to conventional school gymnastics programs for improving children's physical fitness. The integration of traditional games into structured physical education contributes new practical insights for enhancing student engagement, discipline, and psychomotor development in Indonesian primary education contexts.